The development strategy of organic rice farming in Bantul Regency, Special Region of Yogyakarta, Indonesia - Istiyanti, Eni; Anitasari, Dian Widi; Zainal Abidin, Nadiah (2023)
The development of organic rice is also supported by the development of agricultural technology such as compost processing, biological pesticides, agricultural machinery. The conversion of agricultural land in Bantul Regency is unavoidable and has increased. This will have an impact on the development of organic rice farming. This study aims to formulate a strategy for developing organic rice in Bantul Regency based on internal and external factors. This research was conducted in Bantul Regency with the consideration of the most extensive Sustainable Food Agricultural Land. Respondents in this study amounted to 15 people including administrators of organic rice farmer groups, combined farmer groups, organic rice traders, field agricultural extension and Department of Agriculture. The stages in formulating a strategy for developing organic rice farming are (1) Data Collection Stages: IFAS (Internal Factors Strategy Analysis) and EFAS (External Factors Strategic Analysis); (2) Data Analysis Stages: SWOT matrix, and (3) Decision Making Stages: QSPM matrix. The results showed that the strategy that becomes a priority for the development of organic rice farming are skills training for organic rice farmers in farming management and marketing and use of natural resources potential in controlling plant pest organisms of organic rice.